Pengaruh Variasi Penambahan Magnesium Pada Paduan Aluminium Terhadap Konduktivitas Termal Bahan - Angga Wira Putra, I Gusti Ngurah Agung; Astika, I Made; Sukadana, I Gusti Ketut (Teknik Desain Mekanika; Vol 10 No 3 (2021): Juli 2021 : Teknik Desain Mekanika, 2021)
Abstract Aluminum is a metal with excellent thermal conductivity. Aluminum is a lotcombined with various elements magnesium. The motivation behind the investigation was to break down the impact of varieties in the expansion of Magnesium to Aluminum on the warm conductivity of the material. Utilizing the test gear Warmth Move Investigation Base Unit brand TQ. The components of the test examples are 30 mm in breadth and 20 mm thick. The consequence of this exploration is that the warm conductivity will in general diminish with the expansion of magnesium to the aluminum compound. Keywords: Aluminium Alloy,magnesium, thermal conductivity of the materials